EVALUATING FACTORS INFLUENCING MEDICAL CHECKUP ADHERENCE IN PUBLIC SECURITY PERSONNEL USING IMPORTANCE-PERFORMANCE MAPPING (IPMA) METHOD - Pramintasari, Erina; Tan, Pauline H. Pattyranie; Antonio, Ferdi (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
This study analyzing factors influencing adherence to medical checkups among public security personnel, focusing on variables such as Quality of Healthcare Delivery (QHD), Quality of Healthcare Personnel (QHP), Adequacy of Healthcare Resources (AHR), and Quality of Administrative Process (QAP), along with the mediating roles of Quality of Healthcare Environment (QHE) and Patient Satisfaction. A cross-sectional survey method was deployed, involving 185 respondents from security institutions who have experience undergo medical check-up in the institution clinics. Data analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Importance-Performance Mapping Analysis (IPMA). The study found that QHD and QHP were the most importance factors of medical checkup adherence, while AHR and QAP had moderate importance. IPMA results revealed that, while healthcare delivery performed well and should be maintained, personnel quality needed improvement to boost adherence rates. The findings suggest that targeted improvements in healthcare personnel engagement and process efficiency could enhance compliance with medical checkups, ultimately contributing to better health outcomes for security personnel. This research provides actionable insights for healthcare administrators and policymakers, emphasizing the need to prioritize the quality of healthcare delivery and personnel in managing public security health effectively.